Structure design and gait transition stability of quadruped robot - Chen, J.; San, H. (13th International Conference on Quality, Reliability, Risk, Maintenance, and Safety Engineering (QR2MSE 2023), 2023)
In a manner akin to mammals, quadruped robots must select specific gaits corresponding to the terrain in order to curtail energy consumption and enhance ambulatory efficiency. Gait transition, constituting a pivotal facet of quadrupedal robot locomotion research, profoundly embodies the robot's motion prowess. Effectuating real-time gait adjustments while ensuring seamless transition stands as a formidable undertaking, encompassing the investigation into gait transition stability. Presently, within the realm of trajectory planning predicated upon a model, the transition point exhibits abrupt shifts upon immediate completion of gait transition at a designated juncture. This phenomenon substantially undermines the stability of the robot's ambulation process. This paper undertakes the design of a prototype platform for the KUST-canine quadruped robot by assimilating principles from bionics and mechanical engineering. Focusing on the robot as the subject of inquiry, a methodology involving a compound cycloid foot trajectory is introduced. This methodology introduces a variable control approach during the transition phase, enabling consistent speed and adaptable step length both preceding and following gait transformation. Coalescing ADAMS-Simulink co-simulation experiments with prototype trials, the study attests to the quadruped robot's capacity to traverse steadily in alignment with the proposed algorithm. Evidenced by the ability to seamlessly effect gait transitions, the algorithm's efficacy is firmly established.